1997
DOI: 10.1590/s0034-89101997000600007
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre patogenicidade do Schistosoma mansoni em camundongos e susceptibilidade do molusco vetor. IV - Infecciosidade dos miracidios

Abstract: OBJETIVO: Comparar a capacidade de infecção de miracídios das linhagens BH e SJ de S. mansoni, obtidos de camundongos infectados com cercárias oriundas de Biomphalaria glabrata e B. tenagophila, selecionadas geneticamente para a susceptibilidade, com miracídios obtidos de camundongos infectados com larvas procedentes de moluscos não selecionados. MATERIAL E MÉTODO: Progenies de S. mansoni foram obtidas das passagens sucessivas pelos moluscos selecionados, obtendo-se assim gerações de miracídios selecionados. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…Paraense et al (1983) also pointed out that "the presence of B. glabrata is coincident with the schistosomiasis transmission". Thus, these observations have important epidemiological implications, as Zanotti-Magalhães et al (1997) demonstrated that the human disease caused by S. mansoni that use B. glabrata as an intermediate host is more dangerous than that involving B. tenagophila. Despite all the epidemiological implications and also despite the low efficiency as a vector of S. mansoni, B. tenagophila plays a potential and important role together with B. glabrata in transmission of schistosomiasis in different Brazilian regions.…”
Section: Discussionmentioning
confidence: 99%
“…Paraense et al (1983) also pointed out that "the presence of B. glabrata is coincident with the schistosomiasis transmission". Thus, these observations have important epidemiological implications, as Zanotti-Magalhães et al (1997) demonstrated that the human disease caused by S. mansoni that use B. glabrata as an intermediate host is more dangerous than that involving B. tenagophila. Despite all the epidemiological implications and also despite the low efficiency as a vector of S. mansoni, B. tenagophila plays a potential and important role together with B. glabrata in transmission of schistosomiasis in different Brazilian regions.…”
Section: Discussionmentioning
confidence: 99%
“…Adult Biomphalaria tenagophila snails (both susceptible and nonsusceptible) were originally selected by autofertilization of mollusks from parental down to F4 generations with infection rates of 15% and 78% respectively with SJ strains of S. mansoni miracidia acording to ZANOTTI-MAGALHÃES et al 18 They were maintained, as stock cultures, in glass aquaria containing snail conditioned water (SCW-pH 7.8 at ~30 °C), with a density of 10 snails/L. The snails were fed lettuce leaves.…”
Section: Snails Maintenancementioning
confidence: 99%
“…De acordo com Paraense e Correa (1963), B. glabrata é considerado um agente transmissor modelo, provavelmente por causa de adaptações fi siológicas entre o molusco e a cepa local do parasita. Mais ainda, experimentos realizados por Zanotti- Magalhães et al (1997) com espécimes coletados em Belo Horizonte (MG) confi rmaram o alto potencial como vetor atribuído a B. glabrata.…”
Section: Introductionunclassified